Analisis Struktur Organisasi dan Efektivitas Komunikasi Internal: Studi Kasus pada Google Inc - Feliana, Hana; Hermiati; Amanda, Intan Nova Putri; Aisyah, Siti Nur; Surman (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the organizational structure and effectiveness of internal communication at Google Inc., focusing on the relationship between organizational structure, communication mechanisms, and coordination effectiveness in supporting corporate innovation. The study employed a literature study method, analyzing secondary sources in the form of scientific journals, academic books, company reports, and relevant scientific articles. The analyzed literature was published between 2015 and 2025 and selected based on its relevance to the themes of organizational structure, internal communication, organizational behavior, and technology company management. The analysis was conducted through identification, selection, classification, and thematic synthesis of findings from various sources. The study results indicate that Google's organizational structure combines division by function and product with cross-unit coordination, thus supporting collaboration, flexibility, and innovation. The effectiveness of internal communication is demonstrated through information transparency, cross-hierarchical communication, and the use of digital platforms that accelerate information exchange and work coordination. The study also found that formalization through procedures and policies serves as a control mechanism without completely limiting employee creativity. Thus, Google's organizational effectiveness is supported by the relationship between a flexible structure, open internal communication, and an organizational culture that encourages collaboration and innovation.